Pljuča varilcev - Kern, Izidor (Zdravniški vestnik, 2010)
Background: Welders' lung is a pneumoconiosis of benign clinical course following inhalation exposure to welding fumes. It represents the deposition of iron oxides in the lungs. The purpose of this study was to highlight the occupational history, appropriate diagnostic work-up and proper action after the established diagnosis. Methods: We investigated fi ve patients, longterm welders who were admitted to our hospital in the last two years because of possible interstitial lung disease. They underwent bronchoscopy with transbronchial biopsy and bronchoalveolar lavage, high resolution computed tomography of chest and pulmonary function testing. Results: The patients weremale, non- or exsmokers, with a long history of occupational exposure to welding. The most common symptom was dyspnea on eff ort, accompanied with productive cough. Pulmonary function tests showed no abnormalities. HRCT disclosed centrilobular ground glass nodular opacities. Macrophagic reaction with positive stainig for iron was present in bronchoalveolar lavage. In lung tissue, we observed intense iron deposition with no fibrosis. Patients were discussed together with occupational medical doctor. They were advised to stopthe exposure. Conclusions: This study confirms that longterm welders may have symptoms with no functional disorders, but with prominent morphological changes. The key to correct diagnosis is an occupational history of the patient. Diagnostic work-up includes funda mental procedures in suspected interstitial lung disease. The best therapy is cessation of exposure.
Keywords: Biopsija; Biopsy; Bronchoalveolar Lavage Fluid; Bronchoscopy; Bronhoalveolarni izpirek, tekočina; Bronhoskopija; Diagnosis; diagnostika; Lung Diseases, Interstitial; Pathology; pljučne bolezni; Pljučne bolezni intersticijske; Pneumoconiosis; Pnevmokonioza; poklicne bolezni; Thoracic Radiography; varilci; Varjenje; Welding